E–Learning in Extension Systems: Empirical Study in Agricultural Extension in India (Indian Journal of Extension Education, 2010)
E-learning is deciphered as an effective tool to disseminate knowledge and information and has become the boom to the end users. Indian agriculture is witnessing many changes and to meet the challenges, extension system of the country needs to look for alternate ways of learning and training opportunities. In the recent past, Information and Communication Technologies (ICTs) have been seen as potential tools to enhance the system efficiency and meeting the developmental goals. India has one of largest extension system where in more than nine million extension workers functioning under public sector. ICT’s can help in enabling extension workers to gather, store, retrieve, adapt, localize and disseminate a broad range of information needed by farmers, thus transforming them from extension workers to knowledge workers. Rice being the staple crop of India and grown widely requires more attention in order to generate learning opportunities in the public sector extension. Traditional knowledge flow mechanisms may not cater to the existing and emerging needs of the stakeholders. A continuous 24 X 7 training support must be made available based on the requirements of the need based stakeholders. While introducing the e-learning strategies in agriculture, there are few issues to be considered. Such issues include e-readiness of public sector extension, information literacy behavior, etc., The study is mainly based on the results on e-readiness assessment among the extension personnel in rice growing regions of Andhra Pradesh, a South Indian Province.